2022
DOI: 10.3390/jpm12050680
|View full text |Cite
|
Sign up to set email alerts
|

LungNet22: A Fine-Tuned Model for Multiclass Classification and Prediction of Lung Disease Using X-ray Images

Abstract: In recent years, lung disease has increased manyfold, causing millions of casualties annually. To combat the crisis, an efficient, reliable, and affordable lung disease diagnosis technique has become indispensable. In this study, a multiclass classification of lung disease from frontal chest X-ray imaging using a fine-tuned CNN model is proposed. The classification is conducted on 10 disease classes of the lungs, namely COVID-19, Effusion, Tuberculosis, Pneumonia, Lung Opacity, Mass, Nodule, Pneumothorax, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(34 citation statements)
references
References 64 publications
0
15
0
Order By: Relevance
“…Among the 63 studies, 56 studies identified pneumothorax on chest radiography [ 26 81 ], four studies on computed tomography [ 82 85 ], one study on ECG [ 86 ], one study used chest radiography and photography using a smartphone [ 87 ], and one study used chest radiography and tabular data [ 88 ]. Six studies developed and internally tuned DLs [ 37 , 52 , 63 , 67 , 74 , 76 ], 25 studies also internally tested their DLs [ 32 , 33 , 35 , 38 , 40 , 41 , 43 , 45 , 47 , 48 , 50 , 55 , 60 , 65 , 69 , 70 , 73 , 75 , 79 83 , 85 , 86 ] and 32 studies externally tested the DLs [ 26 31 , 34 , 36 , 39 , 42 , 44 , 46 , 49 , 51 , 53 , 54 , 56 59 , 61 , 62 , 64 , 66 , 68 , 71 , 72 , 77 , 78 , 84 , 87 , 88 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Among the 63 studies, 56 studies identified pneumothorax on chest radiography [ 26 81 ], four studies on computed tomography [ 82 85 ], one study on ECG [ 86 ], one study used chest radiography and photography using a smartphone [ 87 ], and one study used chest radiography and tabular data [ 88 ]. Six studies developed and internally tuned DLs [ 37 , 52 , 63 , 67 , 74 , 76 ], 25 studies also internally tested their DLs [ 32 , 33 , 35 , 38 , 40 , 41 , 43 , 45 , 47 , 48 , 50 , 55 , 60 , 65 , 69 , 70 , 73 , 75 , 79 83 , 85 , 86 ] and 32 studies externally tested the DLs [ 26 31 , 34 , 36 , 39 , 42 , 44 , 46 , 49 , 51 , 53 , 54 , 56 59 , 61 , 62 , 64 , 66 , 68 , 71 , 72 , 77 , 78 , 84 , 87 , 88 ].…”
Section: Resultsmentioning
confidence: 99%
“…As for model development, to generate a reference standard for image labelling, 18 studies used expert consensus [ 27 33 , 35 38 , 49 , 53 55 , 71 , 77 , 83 ], two relied on the opinion of a single expert reader [ 76 , 85 ], 16 used pre-existing radiological reports or other imaging modalities [ 34 , 41 , 43 , 45 , 46 , 52 , 60 , 61 , 67 , 75 , 78 82 , 87 ], one study defined their reference standard as surgical confirmation (indicated for surgery) [ 86 ], 11 studies used mixed methods (any combination of the aforementioned) [ 40 , 47 , 48 , 50 , 51 , 62 , 63 , 65 , 69 , 70 , 73 ] and two studies did not report how their reference standard was generated [ 74 , 88 ]. As for model testing, to generate a reference standard for image labelling, 26 studies used expert consensus [ 26 28 , 30 33 , 38 , 39 , 44 , 51 , 54 57 , 61 , 64 , 66 , 68 , 71 73 , 77 , 80 , 83 , 84 ], two relied on the opinion of a single expert reader [ 58 , 85 ], 11 used pre-exist...…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Deep learning has developed rapidly in recent years, making it possible to automatically extract information in the medical field from diagnoses using medical imaging and pattern analysis [ 9 , 10 , 11 , 12 , 13 , 14 , 15 ]. Deep neural networks (DNNs), a type of deep learning, have been widely applied to medical images because of their high performance in detection, classification, and segmentation [ 16 , 17 , 18 , 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%